Impact of Vitamin E on Reducing Primary Dysmenorrhea among University Students: A Single-Blind Randomized Controlled Trial - Maha Abdulaziz; Abdullah A. Almikhlafy; Afnan Almagrami; Rawan Al-Hakimi; Abrar Alrimi; Marwa Al-Maqtari; Asmaa Al Barakani; Khadija Alrazzqe; Mahmoud Alhammadi (University of Science and Technology, Sana’a, Yemen, 2023)
Background: Primary dysmenorrhea is a common complaint among adolescent girls and women of reproductive age, which can be severe enough to negatively affect the quality of their life. Therefore, the present study aimed to assess the impact of vitamin E on primary dysmenorrhea severity among university female students. Methods: This single-blind, randomized controlled trial was conducted on 82 female university students with primary dysmenorrhea, who were allocated to either an intervention group (vitamin E) or a comparison group (placebo) and treated during two successive menstrual cycles. Dysmenorrhea severity was measured using the Visual Analogue Scale at baseline and during the two cycles. Results: The median dysmenorrhea scores were not significantly different between both groups at baseline or during the first cycle after the intervention. However, the median dysmenorrhea score was significantly reduced in the vitamin E group during the second cycle. Most students in the vitamin E and placebo groups had moderate dysmenorrhea at baseline, being 73.2% and 85.4%, respectively. During the first and second cycles after the intervention, most students in the vitamin E group had mild dysmenorrhea (56.1% and 61%, respectively), while most students in the placebo group had moderate dysmenorrhea (58.5% and 56.1%, respectively). Conclusion: Vitamin E can significantly reduce the severity of primary dysmenorrhea when administered in doses of 200 mg twice daily for two days before menstruation and three days thereafter.